EVALUASI PENGARUH KESESUAIAN TERAPI HIPERTENSI DENGAN GUIDELINE JNC 7 TERHADAP TERCAPAINYA TARGET TEKANAN DARAH PASIEN DI RS PANTI WALUYO SURAKARTA PERIODE JANUARI-DESEMBER 2013 - Dian Anggraini, Truly; Puspita Sari, Ika; Probosuseno (Jurnal Farmasi (Journal of Pharmacy), 2016)
Hypertension is a major public health problem worldwide and is the most common risk factor for cardiovascular disease. The prevalence of hypertension in the population aged 18 years and above at 29.8%. Epidemiological data indicates that an increase of blood pressure would improve cardiovascular events. Therefore, hypertension should be treated appropriately by controlling blood pressure. This research aims to evaluate the effect of appropriateness of therapy hypertension based on JNC7 guideline in order to gain targeted blood pressure in RS Panti Waluyo Surakarta during January-December 2013. This study conducted using cohort retrospectively in inpatients medical record in RS Panti Waluyo Surakarta. A total of 116 samples were analyzed with descriptive-analytic method. Both monotherapy and combination of anti-hypertension drug were analyzed with JNC 7 guideline while the target blood pressure were statistically analized using Chi-square test. This research result showed that 50 patients exhibited the appropriate anti-hypertension therapy, while 66 patients showed the inappropriate anti-hypertension therapy. The pattern of anti-hypertension was that 38 patients prescribed single anti-hypertension medicine, 34 patients prescribed combination of 2 anti-hypertension medicine. Like the patients in appropriate group (66%), there were (47%) patients in inappropriate group could achive the target of blood pressure. In conclusion, there is a significant relationship between appropriateness of anti-hypertension use and target blood pressure (p <0.05).